Image and video processing methods, functionalities and services - Sanders, Anna (Willford Press, 2016)
Image processing is a vast field of science that has undergone rapid developments in the recent times. This book unfolds the innovative aspects of image processing which will be crucial for the progress of this field in the future. This book presents a coherent overview of the field through latest researches on innovative image processing techniques such as wavelets, classification, identification, protection, restoration of images, etc. Those in search of information to further their knowledge about image and video processing will be greatly assisted by this book. It is an excellent resource guide for experts as well as students.